POTENSI MIKROORGANISME SEBAGAI BIOFERTILIZER - Lusia Widiastuti; Y. Sulistiyanto; Adi Jaya; Yusurum Jagau; Liswara Neneng (EnviroScienteae, 2019)
This research was carried out in the oil palm plantation of PT. MuliaSawitAgro Lestari (PT. MSAL) Gunung Mas Regency Central Kalimantan Province for 3 months starting in January 2019 until March 2019. The purpose of this study was to identify the potential of microorganisms as biofertilizers from palm oil mill effluent (PKS). This research is an exploratory study conducted in the Laboratory of the Faculty of Health Sciences of the Muhammadiyah University of Palangka Raya. This study used 3 (three) media used to identify the potential of microorganisms for biofertilizer from palm oil liquid waste by calculating the number of bacterial colonies namely Carboxy Methyl Cellulose (CMC), pykovskaya media and Yeast Extract Mannitol Agar (Yema) media. The results of the analysis also showed that PKS liquid waste contained potential microorganisms found were phosphate solvent bacteria, cellulite fungi and nitrogen-fixing bacteria with an average bacterial colony of 1,700,000 cells/mL. Potential microorganisms from the proportion obtained showed the ability of bacteria found in PKS liquid waste to degrade the oil. The first and second samples of bacterial forms identified were in the form of bacilli and were gram-positive bacteria, while the samples of the three bacteria were in the form of coccus and the bacteria were gram-negative bacteria.